Implementasi Rogram Pemberdayaan Gabungan Kelompok Tani Dalam Mencapai Swasembada Beras (Studi Kasus di Badan Ketahanan Pangan Kabupaten Madiun) - Yakti, Kuncoro (Jurnal Administrasi Publik, 2014)
Abstract: Implementation of the Joint Farmers Empowerment Programme Achieving Self-Sufficiency in Rice (Case Studies in Food Security Agency Madiun County). Madiun County one of the districts in East Java, which puts the combined group as an important institution in the development of agriculture. This study shows that, empowerment of farmer groups to improve the self-sufficiency of rice include: strengthening community food distribution agencies, selling delay systems, food storage development community. The program is very helpful in maintaining the stability of grain prices, protect farmers from lack of food availability and the scarcity of time and knowledge enhance the ability of farmers to manage agricultural products. Factors supporting the program is the presence of government regulation, the quantity of human resources, good bookkeeping process. While inhibiting factor is the quality of the resources of humans, lack of fund, lack of a network. Suggestions for the program include creating a network of marketing, post-harvest training and organization of human resources, improvement of monitoring programs as well as, increase the allocation of funds agricultural programs.   Keywords: program, empowerment, joint farmers, rice self-rufficiency, Madiun   Abstrak: Implementasi Program Pemberdayaan Gabungan Kelompok Tani dalam Mencapai Swasembada Beras (Studi Kasus di Badan Ketahanan Pangan Kabupaten Madiun). Kabupaten Madiun salah  satu kabupaten di Jawa Timur yang menempatkan gabungan kelompok tani sebagai institusi penting dalam pembangunan pertanian. Penelitian ini menunjukkan bahwa, program pemberdayaan gabungan kelompok tani dalam meningkatkan swasembada beras antara lain: penguatan lembaga distribusi   pangan   masyarakat, sistem tunda jual, pengembangan lumbung pangan masyarakat. Program  tersebut sangat membantu dalam menjaga kestabilan harga gabah, melindungi petani dari kekurangan ketersediaan pangan waktu paceklik dan meningkatkan kemampuan dan pengetahuan petani dalam mengelola hasil pertanian. Faktor pendukung program tersebut adalah adanya regulasi pemerintah, kuantitas Sumber daya manusia, proses pembukuan yang baik. Sedangkan   faktor   penghambatnya   adalah   kualitas   sumber daya manuasia,   terbatasnya   dana program, minimnya jaringan . Saran untuk program tersebut antara lain menciptakan jaringan pemasaran, pelatihan pasca panen dan organisasi sumber daya manusia,   peningkatan   pengawasan   program   serta,  memperbesar  alokasi   dana program pertanian.   Kata kunci : program, pemberdayaan, gabungan kelompok tani, swasembada beras, Madiun